2014
DOI: 10.1017/s1466252314000231
|View full text |Cite
|
Sign up to set email alerts
|

Results of the BRD CAP project: progress toward identifying genetic markers associated with BRD susceptibility

Abstract: The Bovine Respiratory Disease Coordinated Agricultural Project (BRD CAP) is a 5-year project funded by the United States Department of Agriculture (USDA), with an overriding objective to use the tools of modern genomics to identify cattle that are less susceptible to BRD. To do this, two large genome wide association studies (GWAS) were conducted using a case:control design on preweaned Holstein dairy heifers and beef feedlot cattle. A health scoring system was used to identify BRD cases and controls. Heritab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The Bovine Respiratory Disease Coordinated Agricultural Project aims to identify loci associated with BRD susceptibility and use this information to reduce the disease prevalence in beef and dairy cattle through selective breeding 1 . A GWAS identified SNPs that accounted for 20% of the variation in BRD incidence in dairy cattle, and 17–20% of the variation in clinical signs ( Van Eenennaam et al, 2014 ). Moderate heritability estimates of 21% for either California or New Mexico populations strongly indicated that genomic selection could be used to reduce BRD prevalence in Holstein dairy cattle ( Neibergs et al, 2014b ).…”
Section: Breeding Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Bovine Respiratory Disease Coordinated Agricultural Project aims to identify loci associated with BRD susceptibility and use this information to reduce the disease prevalence in beef and dairy cattle through selective breeding 1 . A GWAS identified SNPs that accounted for 20% of the variation in BRD incidence in dairy cattle, and 17–20% of the variation in clinical signs ( Van Eenennaam et al, 2014 ). Moderate heritability estimates of 21% for either California or New Mexico populations strongly indicated that genomic selection could be used to reduce BRD prevalence in Holstein dairy cattle ( Neibergs et al, 2014b ).…”
Section: Breeding Programsmentioning
confidence: 99%
“…Further studies are being undertaken to uncover the causative SNPs, the role of CNV, the impact of pathogens on gene expression that contributes to disease development, as well as age influence on BRD susceptibility in different breeds ( Neibergs et al, 2014b ). The same group estimated that reducing incidence of BRD to 0.05% by breeding more robust dairy cattle could increase net margins by up to 16%, amounting to $1-2 million in annual savings in U.S. alone ( Neibergs et al, 2014c ; Van Eenennaam et al, 2014 ).…”
Section: Breeding Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Working with Holly Neibergs and Chris Seabury, former members of my lab, was especially pleasing. Using genomic and informatics tools I could have never imagined when these students were in my lab, we have genotyped several thousand dairy and beef animals (diseased and controls) with high-density SNP chips, have found more than 100 genomic regions associated with disease, and have targeted high-priority candidate genes in the dairy population (91,92). Although data collection is completed, considerable analysis remains to be done, especially with beef cattle.…”
Section: Postsequencingmentioning
confidence: 99%
“…49 Thus, progress in BRD research is at an impasse and continued investigations focusing on independent elements (ie, pathogen or host) are unlikely to result in major breakthroughs in BRD research. This situation has been well recognized, and research focusing on identification of markers associated with genetic resistance to BRD has been initiated through the Bovine Respiratory Disease Coordinated Agricultural Project (BRD CAP), 50 which will among other data generate gene expression profiles for single-agent challenge using the majority of BRD pathogens. 51 For field application, diagnostic criteria that allow early disease identification and assessment of lung damage would allow treatment strategies to be tailored to the condition and help identify animals with poor predicted outcomes, similar to the way procalcitonin has been advocated for use in human bacterial lung infections.…”
Section: Existing Measures For Brd Diagnosismentioning
confidence: 99%